EFSUMB Guidelines on Interventional Ultrasound (INVUS), Part I – General Aspects (Short Version) - Lorentzen, T.; Nolsøe, C. P.; Ewertsen, C.; Nielsen, M. B.; Leen, E.; Havre, R. F.; Gritzmann, N.; Brkljacic, B.; Nürnberg, D.; Kabaalioglu, A.; Strobel, D.; Jenssen, C.; Piscaglia, F.; Gilja, O. H.; Sidhu, P. S.; Dietrich, C. F. (Ultraschall in der Medizin - European Journal of Ultrasound, 2015)
This is the first part of the Guidelines on Interventional Ultrasound of the European Federation of Societies for Ultrasound in Medicine and Biology (EFSUMB) and covers all general aspects of ultrasound-guided procedures (short version; the long version is published online).
Keywords: guideline; ultrasound guidance; hygiene; microbiology; safety